Adapting Social Work Education to Address Climate Change in Pakistan: Curriculum Reform, Climate Justice, and Community Resilience - Dr. Sadia Rafi; Dr. Mumtaz Ali (Social Science Review Archives, 2025)
In Pakistan, climate change has exacerbated social vulnerabilities which are experienced disproportionately by the marginalized populations in form of regular floods, heatwaves, droughts, displacement, food insecurity and disruption of livelihoods. Research Objectives of the study include: To investigate the level at which the concepts of climate change, environmental sustainability and climate justice have yet to be incorporated into the Pakistani university social work curricula. To determine the areas of knowledge, skills and pedagogical methodology gaps in current social work education that restrict the ability of practitioners to respond to social vulnerabilities and challenges related to a disaster caused by climate change. To suggest a contextualized curriculum redesign framework, which incorporates climate justice principles and community resilience approach in social work education in Pakistan. The proposed study has a qualitative research design to understand how the education of social work in Pakistan can be changed to mitigate climate change by changing the curriculum and incorporating climate justice. The use of an exploratory and descriptive approach is explained by the fact that not much empirical studies have been conducted on the topic of environmental social work education in Pakistan. Exploratory research can be used in the research that explores an underdeveloped field of study. The research will be carried out within some Pakistani institutions that run social work programs. The participants will be social work faculty, curriculum developers, administration, field supervisors and final year students. The input of data is collected using semi-structured interviews, focus group discussions, and document analysis. Interviews enable the participants to give experiences and institutional information Data are analyzed in the framework of thematic analysis. Inductive coding of the transcripts is done to discern patterns based on curriculum reform, climate justice, and resilience. The codes are grouped into more general themes that denote institutional strengths and weaknesses. The approach guarantees an orderly and stringent qualitative interpretation.